Preoperative evaluation for gynecologic surgery: a guide to judicious, evidence-based testing. Issue 4 (August 2018) - Shields, Jessica; Lupo, Andrew; Walsh, Teresa; Kho, Kimberly
Abstract : Purpose of review: Preoperative testing is a routine component of surgical planning, however, the majority of literature agree that laboratory and diagnostic studies are over utilized. We aim to summarize the available literature and provide gynecologists performing elective surgery for benign indications guidance to determine when, in whom, and in what time frame preoperative studies should be collected. Recent findings: Current literature supports previous publications indicating routine laboratory and diagnostic testing for elective surgery is unnecessary and continues to be excessive. The frequency of abnormal results is high, whereas the impact on surgical planning and outcomes is negligible. Summary: The preoperative evaluation including thorough history and physical examination should be the cornerstones for eliciting underlying disease, which may alter a surgical strategy. Devising a protocol to direct preoperative testing has been shown to decrease unnecessary tests without compromising prediction of perioperative morbidity/mortality or case cancellation and changes. Avoidance of 'routine preoperative testing' and instead, thoughtful risk stratification of individual patients, should be a goal of providing value-based care.